PROFESSIONAL ORIENTATION OF MATHEMATICAL TRAINING FOR A FUTURE ENGINEERS - Opaeva Gulbakhar Aymanovna; Rametullaev Dabil Danebayevich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. The introduction of new high technology in the development of the oil and gas complex significantly increases the requirements in the field of basic sciences for graduates of higher educational institutions of engineering profile.